The status of Inland Fishery in Dhi Qar Province during the period from 2017 to 2020 - Nasir, Noori A.; Sultan, Qasim M. (Mesopotamian Journal of Marine Sciences, 2022)
An investigation was carried out to overview the status of the inland fishery resources in Dhi Qar Province during the period from 2017 to 2020. The whole fish landed from five marshes throughout the study period was about 30833 tons using seine net, gill net, cast net and electro-fishing gears. The highest annual quantity landed was about 8502 tons in 2020 which formed about 27.6 % of total fish landed. In fact, this variation in fish stock from year to year could be related to overfishing, weather changes, pollution levels, water levels, market prices and environmental conditions (natural or human-made). This study also indicated that the majority of fish landed came from capture fisheries and the rest from fish farming. Eleven fish species were observed and Cyprinus carpio was dominant with 37 % of the total weight landed followed by Planiliza abu which comprised about 25% of the total. Six native species, two alien species and two migratory species were also found throughout this investigation which composed about 41.3 %, 56.5 % and 2.2 % of the total, respectively.